Identifying the Attributes of College Students' Fast Food Restaurant Selection and Satisfaction - Sunghyup Hyun(현성협); Kunsoon Park(박근순); Yoonjoung Heo(허윤정) (동아시아식생활학회지, 2010)
College students represent a substantial market for fast food restaurant companies. In this sense, this research aims (1) to identify the attributes that influence college students' fast food restaurant selection, (2) to analyze how fast food restaurants perform with regards to those attributes using importance-performance analysis, and (3) to examine which attributes influence college students' satisfaction in a fast food restaurant context. Based on a literature review, 13 attributes that influence college students' fast food restaurant selection were derived. Then, using importance-performance analysis, it was found that among the 13 attributes, college students highly considered seven of them. Additionally, data analysis indicated that, currently, fast food companies perform well with regards to these seven attributes. More importantly, according to multiple regression analysis, among the seven attributes, value-related attributes (price, speed, location, and friendliness) were significantly related to college students' overall satisfaction. KCI Citation Count: 1